Polydimensional Structure and Psychosocial Functions of the Direct Address in TV Series - Galimberti, Carlo; Bova, Antonio; Spanò, Carmen; Vergine, Ilaria (Frontiers in Psychology, 2021)
Traditionally, in media studies research, the direct address or aside, i.e., a construction in which a speaker communicates a message directly to the audience breaking the continuity of the narrative flow, has been investigated mainly for its dramaturgical function. The present study aims to consider the direct address as a research object of the social psychology of communication to increase our understanding of this technique by going beyond the analysis of its dramaturgical function. The direct address will be examined through an integrated approach based on argumentative and conversational tools to highlight its less known polydimensional structure, i.e., diegetic and extra-diegetic dimensions and their interactions, and psychosocial functions, i.e., connecting the characters among each other within the show as well as with the audience. This objective will be achieved by analyzing two different direct addresses from the American TV series House of Cards. The analysis showed that the direct address performs its dramaturgical function by impacting both diegetic and extradiegetic levels. In the first case, as considered in previous studies, these plans are activated in parallel, aiming to build what we have defined as the 'strategic subjectivity' of the character who employs this technique. Instead, in the second case – which comprises two direct addresses produced by two different characters - this technique involves the creation of what we will call 'platforms of intersubjectivity.' In this occurrence, the dramaturgical action establishes a 'bridge' between the diegetic and extradiegetic plans that act synergistically. In conclusion, the present study shows how an integrated approach based on argumentative and conversational tools of analysis permits to enlarge the traditional media studies perspective, highlighting the less investigated polydimensional structure and analyzing the psychosocial functions of the direct address, here considered as a research object of the social psychology of communication. The integration of the pragma-dialectical approach to argumentation with the interlocutory logic theory has brought to light a new modality of use of the direct address that can be termed ‘intersubjective aside,’ a type of aside that can be added to the three already known, i.e., aside ad spectatores, monological aside, and dialogical aside.